Design of two degree of freedom-internal model control configuration for load frequency control using model approximation. (2nd January 2019) - Sonker, Bheem; Kumar, Deepak; Samuel, Paulson
Abstract: In this paper, a modified two degree of freedom-internal model control structure is proposed with dual feedback loop configuration for load frequency control problem of the single area and two area non-reheated power systems to achieve better transient and steady state performance. Predictive model of the proposed configuration is derived through Routh, Padé and SOPDT approximations. Hence, for all three cases, the proposed configuration is simulated considering the single area and two area power systems with non-reheated turbine along with 50% parametric uncertainty. Finally, a comparison with existing techniques is included to validate the effectiveness and performance of the proposed control configuration through responses and error indices. It is observed that the proposed scheme generates better results under parameter variations.